Moderating Effect of Emotional Intelligence on Occupational Stress and Burnout of Health Care Professionals - Tiwari, Swarnima; Bhagat, Deepak (Prabandhan: Indian Journal of Management, 2021)
Front line healthcare professionals are often times confronted with tremendous stress resulting in emotional distress that impacts their success at work. It is understood that individuals with high emotional intelligence perceive potential stressors better and withstand stress. The present study intended to explore the emotional intelligence dimension of health care professionals in dealing with stressful situations. The study included frontline healthcare professionals (doctors and nurses) employed in the West Garo Hills District of Meghalaya. The results revealed that emotional intelligence was negatively correlated with occupational stress. Emotional intelligence was found to moderate perceived stress and burnout. The study revealed the presence of moderate to high levels of high occupational stress and emotional intelligence among doctors and nurses. It was also observed that emotional intelligence moderated perceived stress, emotional exhaustion, and depersonalization dimensions of burnout for both doctors and nurses. The above insights necessitate the requirement of well-developed training modules to improve the emotional intelligence of doctors and nurses. A well carved out training module on emotional intelligence will assist in decreasing the negative effects of job stress, coping up with the stress, and its related burnout faced by health care professionals.